DISEÑO DE UN MANUAL DE CONTROL INTERNO ADMINISTRATIVO Y CONTABLE PARA LA EMPRESA COMERCIAL AUTOSERVICIO PANDA EN LA CIUDAD DE LOJA - Chávez Pullaguari, Sonia Cumanda (2019)
The purpose of this thesis is "DESIGN OF AN INTERNAL ADMINISTRATIVE AND ACCOUNTING CONTROL MANUAL FOR THE PANDA AUTOMOTIVE COMMERCIAL ENTERPRISE IN THE CITY OF LOJA", this research was carried out with the purpose of presenting alternatives to solve the problems related to the various internal control weaknesses existing in said company. To comply with the investigative work, we opted to conduct interviews with the company's Manager and Accountant, in order to gather necessary information about the current reality in which the activities are carried out within it. The Internal Control has as objective to show how the company is operating, as a result of this investigation the organizational structure was determined, the establishment of the internal control components and finally the procedures and activities of internal control that attributed to the improvement were designed. of the company. The general objective proposed is "Design an internal administrative and accounting control manual for the Panda Self-Service Business Company, located in the parish of San Sebastián in the city of Loja, province of Loja, which is complied with under the following specific objectives . 5 In order to comply with the first specific objective of the design of an internal administrative and accounting control manual, it was done through the application of the interview to the manager, which was very important, since the business and functional organizational chart of the same With the second objective, the factors of the components of internal control, environment and control activity were established, being the most outstanding in the investigative process. The third specific objective was achieved through the flow diagrams, procedures and activities of the company, clearly detailing the obligations and responsibilities that must be met, reducing unnecessary activities and contributing to the development of the company. At the end of the research work, the conclusions and recommendations were formulated with the sole purpose of helping the goals and objectives proposed by the Panda Self-Service Company to be met at the end of the year, and this help to make decisions based on the results obtained during the investigative process through effective internal control.